MODERN APPROACHES TO DIAGNOSTICS AND PHYSICAL THERAPY OF UPPER EXTREMITY MOVEMENT FUNCTION IN CHILDREN WITH CEREBRAL PALSY (Physical Culture and Sport: Scientific Perspective, 2025)
The hemiplegic forms of cerebral palsy characterized by a clinical picture of unilateral movement impairment are between 36% and 44% of all cases of the disease. The upper extremity dysfunction can range from mild to severe depending on the timing, location, degree, and nature of the brain injury. These impairments limit the child's ability to perform everyday tasks affecting their participation and quality of life. One of the most popular approaches to the rehabilitation of such impairments is a constraint induced movement therapy. The key components of this therapy are the restraint of the unaffected upper extremity with the addition of intensive practice of task-related movements in the affected extremity.The aim of the study is to investigate the use efficiency of a modified model of constraint induced movement therapy (mCIMT) as a home exercise program in correcting the functional state of the paretic extremity in children with hemiplegic cerebral palsy.The study involved 24 children with hemiplegic cerebral palsy aged 7-10 years who were randomly divided into a main and a control group consisting of 12 individuals. The manual abilities of all children were classified according to the Manual Ability Classification System (MACS) as MACS II level. The children in the main group received 40 hours of intensive training of the paretic extremity mCIMT in an 8-week home training program and 80 hours of forced use, while children in the control group received 40 hours of normal-intensity bimanual training. The use of this approach allowed to significantly improve the quality of skills of the paretic upper extremity in children in the main group compared to the control group in the following domains of the QUEST test (Quality of Upper Extremity Skills Test): in the dissociated movements domain - 82.70±6.15 points versus 73.25±7.84 points (p < 0.05), in the grasping domain - 54.74±7.09 points versus 46.83±5.15 points (p < 0.05), in the weight-bearing domain - 83.06±4.51 points versus 75.83±7.17 (p < 0.05). The positive results of the CIMT models are explained by a higher dose of training which is a key element in improving movement outcomes.
Keywords: cerebral palsy; children; upper extremity; constraint induced movement therapy; homework program; QUEST test